Komitmen afektif anggota Dewan Perwakilan Daerah: Peran kepemimpinan transformasional dan identitas sosial melalui pertukaran sosial: Affective commitment of regional representative council members: The role of transformational leadership and social identity through social exchange - Njoto, Herlina Harsono; Suryanto, Suryanto; Fajrianthi, Fajrianthi (Persona:Jurnal Psikologi Indonesia, 2025)
The phenomenon of “party switching” among members of the Regional House of Representatives (DPRD) in East Java indicates a low level of affective commitment to political parties, which in turn poses a threat to the stability of local democracy. This study examines the effects of transformational leadership and social identity on the affective commitment of DPRD members, with social exchange serving as a mediating variable. Employing a quantitative design using Structural Equation Modeling (SEM), the study involved 287 active DPRD members from cities and regencies in East Java, representing five Regional Coordination Bodies (Bakorwil). The research instruments included the Affective Commitment Scale (α = 0.85), the MLQ Transformational Leadership scale (α = 0.92), the Three-Factor Social Identity scale (α = 0.88), and the Amalgamated Social Exchange scale (α = 0.90). The results indicate that social identity has the strongest influence on affective commitment, followed by transformational leadership, while social exchange was found to partially mediate these relationships. These findings underscore social identity as the primary predictor of commitment within Indonesia’s collectivist political context.